(untitled) (Asian Journal of Medical Sciences, 2025)
Lumbar spondylosis (LS) is a common degenerative spinal condition that contributes significantly to chronic low back pain and disability, particularly in older adults. This case report investigates the effectiveness of neurotherapy as a non-invasive treatment for LS. A 35-year-old woman with magnetic resonance imaging (MRI)-confirmed LS, opted against surgical intervention, and underwent 48 neurotherapy sessions over a 12-week period. The therapy targeted seven specific anatomical zones, aiming to enhance circulation, reduce nerve compression, and improve intervertebral spacing. Post-treatment MRI demonstrated a notable increase in L5-S1 disc space from 3.0 mm to 7.0 mm, indicating reduced spinal compression. In addition, the patient reported significant pain relief and improved mobility. These findings suggest that neurotherapy offers both symptomatic and structural benefits, making it a promising alternative to traditional treatments for LS. This case highlights the potential of neurotherapy as a non-invasive therapeutic option to address the root causes of LS and enhance patient outcomes.